Reverse Solvatochromism in Solvent Binary Mixtures: A Case Study Using a 4-(Nitrostyryl)Phenolate as a Probe - Caroli-Rezende, M (Royal Society of Chemistry, 2016)
A 4-(nitrostyryl)phenolate was synthesized and its use in pure solvents revealed a reversion in solvatochromism. Solutions of a dye in binary solvent mixtures, using as components the solvents in the region of the occurrence of the reversion, provided the first case in the literature of reverse solvatochromism in a binary mixture. © the Owner Societies 2016.